CORRELATION AMONG LEARNING STRATEGIES, EMOTIONAL INTELLIGENCE AND READING ACHIEVEMENT OF THE FIFTH SEMESTER STUDENTS OF STKIP MUHAMMADIYAH KOTABUMI LAMPUNG UTARA ACADEMIC YEAR 2014/2015 - Dewi Sri Kuning (Universitas PGRI Palembang, 2015)
Reading means understanding a written text to get the information and knowledge as efficiently as possible. The foundational skills of reading are: word reading, fluency, vocabulary, and word knowledge. Many students of the fifth semester still get low in reading score. There are many factors that caused the low score of the students, such as: they do not have suitable method in learning English, they are lazy to repeat the material at home, and they have low motivation, and so on. Based on the problem, the researcher wants to investigate the correlation among learning strategies, emotional intelligence, and reading achievement. Furthermore, the population of the research is the fifth semester students of English Education Department of STKIP Muhammadiyah Kotabumi consisting of 85 students, from the population, 50 students were represented as the sample which was taken through simple random sampling technique. The instruments to collect the data used questionnaires for learning strategies and emotional intelligence and test for reading achievement. While to analyze the data, it was used multiple correlation in SPSS 13 Program for Windows. The data analysis shows that Ryx1x2 = 0.391 at the significant level of 0,05. And for the criteria of significant test is gotten Fcount (4.230) > Ftable (0,05) (4,01). The result of hypothesis test showed that there is significant correlation among learning strategies, emotional intelligence, and reading achievement. Therefore, it is suggested that English teachers should teach by giving appropriate strategy and give the good example of emotional intelligence in teaching reading skill. Key words: Learning Strategies, Emotional Intelligence, and Reading Achievement.